Characteristics and controlling factors of coal-measure unconventional reservoirs – A case study of the Carboniferous-Permian in the Ordos Basin - Zengqin Liu; Shihu Zhao; Zongquan Hu; Baojian Shen; Dongjun Feng; Jiaqi Zhang; Jincheng Ye; Chao Ma; Zhaoxiong Dong (Unconventional Resources)
Coal-measure unconventional natural gas exhibits diverse types and abundant resources, making it a strategic exploration field to marine shale gas. Currently, researches on coal-measure unconventional gas are still in the early stages, and further study is needed on the characteristics and controlling factors of coal-measure reservoirs. Taking the Carboniferous and Permian in the Ordos Basin as an example, the maceral observation, total organic carbon, X-ray diffraction, scanning electron microscopy, porosity-permeability testing, high-pressure mercury intrusion, low-temperature liquid nitrogen adsorption, and carbon dioxide adsorption experiments are employed to elucidate the reservoir space types, storage features, pore size distribution, and fractal features of coal-measure unconventional reservoirs. The result shows that coal, carbonaceous shale and argillaceous shale are the main reservoirs in coal-measure strata, and their storage performance are different under the control of total organic carbon (TOC). The main reservoir spaces in coal reservoirs are organic matter pores and cleats, while carbonaceous shale and argillaceous shale reservoirs are dominated by inorganic pores. In addition, the pore volume of coal seam, carbonaceous shale, and argillaceous shale decreases sequentially, of which coal seam features large pore volume, and is rich in micro and macro pores, while argillaceous shale exhibit small pore volumes and relatively high mesopore contents. The fractal dimensions of macropores, mesopores, and micropores sequentially decrease, indicating a weakening heterogeneity. Additionally, the porosity of coal-measure reservoirs is positively correlated with TOC, vitrinite content, and carbonate mineral content, while being negatively correlated with clay mineral content. The fractal dimension is negatively correlated with TOC and positively correlated with clay mineral content, suggesting a strong source-reservoir coupling correlation. Overall, coal-measure reservoirs with higher TOC exhibit the characteristics of “high proportion of organic matter pore, high pore volume, high porosity, and low fractal dimension”. And thick coal seam and carbonaceous shale in the Ordos Basin with higher TOC and porosity provide a material foundation for achieving high production, making them a promising new frontier for unconventional natural gas exploration and development.